2013
DOI: 10.1007/s13346-013-0133-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for CNS delivery of bio-therapeutic agents

Abstract: The current therapeutic strategies are not efficient in treating disorders related to the central nervous system (CNS) and have only shown partial alleviation of symptoms, as opposed to, disease modifying effects. With change in population demographics, the incidence of CNS disorders, especially neurodegenerative diseases, is expected to rise dramatically. Current treatment regimens are associated with severe side-effects, especially given that most of these are chronic therapies and involve elderly population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 97 publications
0
31
0
1
Order By: Relevance
“…[58][59][60] This route involves the olfactory or trigeminal nerve systems, which are initiated from parts of the brain and terminate in the nasal cavity at the olfactory epithelium or respiratory epithelium, all of which bypass the BBB. 61 Other studies have attempted to focus on the nerve conduction velocity in nanomaterials. For example, De Lorenzo 62 reported that gold NPs (50 nm in size) were translocated by the olfactory nerve after nasal administration in the squirrel monkey, and the transfer speed was 2.5 mm/hour.…”
Section: Sensory Nerve Translocation Pathwaymentioning
confidence: 99%
“…[58][59][60] This route involves the olfactory or trigeminal nerve systems, which are initiated from parts of the brain and terminate in the nasal cavity at the olfactory epithelium or respiratory epithelium, all of which bypass the BBB. 61 Other studies have attempted to focus on the nerve conduction velocity in nanomaterials. For example, De Lorenzo 62 reported that gold NPs (50 nm in size) were translocated by the olfactory nerve after nasal administration in the squirrel monkey, and the transfer speed was 2.5 mm/hour.…”
Section: Sensory Nerve Translocation Pathwaymentioning
confidence: 99%
“…The intranasal delivery of nanomedicines may be an interesting option due to the direct nose-to-brain transport, which bypasses the BBB. 111 Another issue is related to the accumulation of antiretroviral drugs and even nanocarriers at the CNS and their potential neurotoxicity, particularly when long-term regimens are needed. The biodistribution patterns of NPs once in the CNS, alongside their long-term fate, also require additional understanding.…”
Section: Conclusion and Remaining Challengesmentioning
confidence: 99%
“…The BBB is a dynamic barrier that protects the brain against unwanted substances, as well as being a barrier to drug transport into the brain from the blood circulation. Despite impressive advances in treatment options, the success rates are still moderate for CNS disorders, including brain tumors, Alzheimer's disease (AD), Parkinson's disease (PD) and stroke [1]. The majority of therapeutic compounds administered to the CNS have inadequate brain uptake owing to low permeability across the BBB or efflux by multidrug resistant (MDR) proteins or unusual plasma protein binding [2].…”
Section: Introductionmentioning
confidence: 99%